In Vitro Killing Activities of Anidulafungin and Micafungin with and without Nikkomycin Z against Four Candida auris Clades - Awid Adnan; Andrew M. Borman; Zoltán Tóth; Lajos Forgács; Renátó Kovács; Dávid Balázsi; Bence Balázs; Gergely Udvarhelyi; Gábor Kardos; László Majoros (MDPI AG, 2023)
Candida auris is a multidrug-resistant pathogen against which echinocandins are the drug of choice. However, information on how the chitin synthase inhibitor nikkomycin Z influences the killing activities of echinocandins against C. auris is currently lacking. We determined the killing activities of anidulafungin and micafungin (0.25, 1, 8, 16 and 32 mg/L each) with and without nikkomycin Z (8 mg/L) against 15 isolates representing four C. auris clades (South Asian n = 5; East Asian n = 3; South African n = 3; South American n = 4, two of which were of environmental origin). Two and one isolates from the South Asian clade harbored mutations in the hot-spot 1 (S639Y and S639P) and 2 (R1354H) regions of the FKS1 gene, respectively. The anidulafungin, micafungin and nikkomycin Z MIC ranges were 0.015-4, 0.03-4 and 2->16 mg/L, respectively. Anidulafungin and micafungin alone exerted weak fungistatic activity against wild-type isolates and the isolate with a mutation in the hot-spot 2 region of FKS1 but was ineffective against the isolates with a mutation in the hot-spot 1 region. The nikkomycin Z killing curves were always similar to their respective controls. Twenty-two of sixty (36.7%) anidulafungin plus nikkomycin Z and twenty-four of sixty (40%) micafungin plus nikkomycin Z combinations produced at least 100-fold decreases in the CFUs (synergy), with a 41.7% and 20% fungicidal effect, respectively, against wild-type isolates. Antagonism was never observed. Similar results were found with the isolate with a mutation in hot-spot 2 of FKS1, but the combinations were ineffective against the two isolates with prominent mutations in hot-spot 1 of FKS1. The simultaneous inhibition of β-1,3 glucan and chitin synthases in wild-type C. auris isolates produced significantly greater killing rates than either drug alone. Further studies are warranted to verify the clinical efficacy of echinocandin plus nikkomycin Z combinations against echinocandin susceptible C. auris isolates.